An overview of methods for deriving the radiative transfer theory from the Maxwell equations. III: Effects of random rough boundaries and packing density. (February 2019) - Doicu, Adrian; Mishchenko, Michael I.
Highlights: Radiative transfer theory. Randomly rough surfaces. Wigner-transform method. Coherent field and the vector radiative transfer equations. Abstract: In this paper we apply the Green function formalism and the Wigner transform method to derive the radiative transfer equation for a layer of sparse discrete random medium bounded by scattering rough interfaces. The radiative transfer equation is formulated with respect to the Wigner transform of the dyadic correlation function for the electromagnetic field. The results are obtained under the effective field and on-shell approximations, and the meaning of these approximations is discussed in detail.